2017
DOI: 10.1158/0008-5472.can-16-2246
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Interactions of EBP1 Isoforms with FBXW7 Elicits Different Functions in Cancer

Abstract: The ErbB3 receptor binding protein EBP1 encodes two alternatively spliced isoforms p48 and p42. While there is evidence of differential roles for these isoforms in tumorigenesis, little is known about their underlying mechanisms. Here we demonstrate that EBP1 isoforms interact with the SCF-type ubiquitin ligase FBXW7 in distinct ways to exert opposing roles in tumorigenesis. EBP1 p48 bound to the WD domain of FBXW7 as an oncogenic substrate of FBXW7. EBP1 p48 binding sequestered FBXW7α to the cytosol, modulati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 51 publications
3
41
0
Order By: Relevance
“…PKC may facilitate cellular transformation by inactivating FBXW7α through cytoplasmic sequestration. Finally, the EBP1 (ErbB3 receptor-binding protein) gene encodes two alternatively spliced isoforms: P48 and P42 [ 86 ]. P48 forms a negative feedback loop with FBXW7α, whereby FBXW7α degrades P48 in a GSK3-dependent manner, and P48 is able to bind FBXW7α and sequester it in the cytosol.…”
Section: Inactivation Of Fbxw7 Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…PKC may facilitate cellular transformation by inactivating FBXW7α through cytoplasmic sequestration. Finally, the EBP1 (ErbB3 receptor-binding protein) gene encodes two alternatively spliced isoforms: P48 and P42 [ 86 ]. P48 forms a negative feedback loop with FBXW7α, whereby FBXW7α degrades P48 in a GSK3-dependent manner, and P48 is able to bind FBXW7α and sequester it in the cytosol.…”
Section: Inactivation Of Fbxw7 Functionsmentioning
confidence: 99%
“…P48 forms a negative feedback loop with FBXW7α, whereby FBXW7α degrades P48 in a GSK3-dependent manner, and P48 is able to bind FBXW7α and sequester it in the cytosol. This prevents FBXW7α from degrading its substrates [ 86 ]. In contrast, P42 acts as an adaptor to stabilize the interaction between FBXW7 and its substrates, which enhances FBXW7-mediated degradation [ 86 ].…”
Section: Inactivation Of Fbxw7 Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Repression of PA2G4 expression was associated with an increase in MYCN ubiquitination. Studies in colorectal cancer cells suggested PA2G4 could bind directly to, and sequester Fbxw7 in the cytoplasm, thus indirectly increasing nuclear MYC protein stability (12). We investigated this potential mechanism of PA2G4 influencing MYCN protein stability indirectly by shifting the location of Fbxw7 toward the cytoplasm and possibly protecting nuclear proteins including MYCN.…”
Section: Pa2g4 and Mycn Exhibit Functionally Interdependent Expressionmentioning
confidence: 99%
“…The proliferation-associated 2AG4 protein (PA2G4), or ErbB3 binding protein (EBP1), binds Fbxw7, sequestering it in the cytoplasm, hence stabilizing MYC in colorectal cancer cells (12). PA2G4 is a ubiquitously expressed DNA and RNA binding protein with roles in normal embryonal muscle and neural crest cell growth (13,14).…”
Section: Introductionmentioning
confidence: 99%